Artesunate derivative TF27 inhibits replication and pathogenesis of an oncogenic avian alphaherpesvirus - Bertzbach, Luca D.; Conradie, Andelé M.; Hahn, Friedrich; Wild, Markus; Marschall, Manfred; Kaufer, Benedikt B. (Antiviral Research, 2019)
Nucleoside analogues have been the cornerstone of clinical treatment of herpesvirus infections since the 1970s. However, severe side effects and emergence of drug resistant viruses raise the need for alternative treatment options. We recently investigated the broad and strong antiherpesviral activity of the optimized artesunate derivative TF27 in vitro. TF27 efficiently inhibited replication of the highly oncogenic Marek's disease virus (MDV), a virus that infects chickens, causes deadly lymphomas and threatens poultry populations worldwide. In this study, we used this natural virus-host model for herpesvirus-induced cancer by infecting chickens with MDV, and evaluated the protective efficacy of TF27 and the nucleoside analogue valganciclovir (VGCV) on virus replication and tumorigenesis. We could demonstrate that both drugs reduced viral load in the blood and prevented tumor development in a large portion of the animals. Antiviral treatment also had a positive impact on body weight gain, while no negative compound-associated side effects were observed. This research provides the first evidence that the artesunate derivative TF27 and VGCV can be used in avian species and that they inhibit MDV replication and tumorigenesis. In addition, our study paves the way for promising approaches in future antiherpesviral drug development.
CRIS-Team Scopus Importer:2019-09-24
Keywords: Artesunate; Artesunate derivative; Experimental antiviral drug; Herpesviral in vivo models; Indirect host-targeted antivirals; Marek's disease virus; NF-κB signaling inhibition

Autofluorescent Artemisinin-Benzimidazole Hybrids via Organo-Click Reaction: Study of Antiviral Properties and Mode of Action in Living Cells - Herrmann, Lars; Hahn, Friedrich; Grau, Benedikt; Wild, Markus; Niesar, Aischa; Wangen, Christina; Kataev, Evgeny; Marschall, Manfred; Tsogoeva, Svetlana (Chemistry - A European Journal, 2023)
Drug modification by a fluorescent label is a common tool for studying its mechanism of action with fluorescence microscopy techniques. However, the attachment of a fluorescent label can significantly alter the polarity, solubility, and biological activity of the investigated drug, and, as a result, the studied mechanism of action can be misrepresented. Therefore, developing efficient drugs, which are inherently fluorescent and can be tracked directly in the cell is highly favorable. Here an easy formation of fluorescent hybrid drugs is presented, generated by a combination of two readily available non-fluorescent pharmacophores via a non-cleavable linker using a Ramachary-Bressy-Wang organocatalyzed azide-carbonyl [3+2] cycloaddition (organo-click) reaction. All newly prepared fluorescent compounds showed strong anti-HCMV activity (EC50 down to 0.07±0.00 μM), thus presenting a very promising drug developmental basis compared to the approved drug ganciclovir (EC50 2.60±0.50 μM). Remarkably, in vitro fluorescent imaging investigation of new compounds revealed induced changes in mitochondrial structures, which is a phenotypical hallmark of antiviral activity. This approach opens up new vistas for the easy formation of potent fluorescent drugs from readily available non-fluorescent parent compounds and might facilitate insight into their mode of action in living cells, avoiding the requirement of linkage to external fluorescent markers.
CRIS-Team Scopus Importer:2023-09-08
Keywords: artemisinin-benzimidazole hybrids; autofluorescent antivirals; confocal microscopy; organo-click reaction; [3+2] cycloaddition

Combinatorial drug treatments reveal promising anticytomegaloviral profiles for clinically relevant pharmaceutical kinase inhibitors (PKIs) - Wild, Markus; Kicuntod, Jintawee; Seyler, Lisa; Wangen, Christina; Bertzbach, Luca D.; Conradie, Andelé M.; Kaufer, Benedikt B.; Wagner, Sabrina; Michel, Detlef; Eickhoff, Jan; Tsogoeva, Svetlana; Bäuerle, Tobias; et al. (International Journal of Molecular Sciences, 2021)
Human cytomegalovirus (HCMV) is a human pathogenic herpesvirus associated with a variety of clinical symptoms. Current antiviral therapy is not always effective, so that improved drug classes and drug-targeting strategies are needed. Particularly host-directed antivirals, including pharmaceutical kinase inhibitors (PKIs), may help to overcome problems of drug resistance. Here, we focused on utilizing a selection of clinically relevant PKIs and determined their anticytomegaloviral efficacies. Particularly, PKIs directed to host or viral cyclin-dependent kinases, i.e., abemaciclib, LDC4297 and maribavir, exerted promising profiles against human and murine cytomegaloviruses. The anti-HCMV in vitro activity of the approved anti-cancer drug abemaciclib was confirmed in vivo using our luciferase-based murine cytomegalovirus (MCMV) animal model in immunocompetent mice. To assess drug combinations, we applied the Bliss independence checkerboard and Loewe additivity fixed-dose assays in parallel. Results revealed that (i) both affirmative approaches provided valuable information on anti-CMV drug efficacies and interactions, (ii) the analyzed combinations comprised additive, synergistic or antagonistic drug interactions consistent with the drugs’ antiviral mode-of-action, (iii) the selected PKIs, especially LDC4297, showed promising inhibitory profiles, not only against HCMV but also other α-, β-and γ-herpesviruses, and specifically, (iv) the combination treatment with LDC4297 and maribavir revealed a strong synergism against HCMV, which might open doors towards novel clinical options in the near future. Taken together, this study highlights the potential of therapeutic drug combinations of current developmental/preclinical PKIs.
CRIS-Team Scopus Importer:2021-01-22
Keywords: Activity in vitro and in vivo; Antiviral drugs; Combinatorial drug analyses; Human cytomegalovirus; New synergistic combinations; Pharmaceutical kinase inhibitors (PKIs)

Combined Treatment with Host-Directed and Anticytomegaloviral Kinase Inhibitors: Mechanisms, Synergisms and Drug Resistance Barriers. - Wild, Markus; Karner, Dubravka; Eickhoff, Jan; Wagner, Sabrina; Kicuntod, Jintawee; Chang, William; Barry, Peter; Jonjić, Stipan; Lenac Roviš, Tihana; Marschall, Manfred (Pharmaceutics, 2023)
Despite the availability of currently approved antiviral drugs, infections with human cytomegalovirus (HCMV) still cause clinically challenging, sometimes life-threatening situations. There is an urgent need for enhanced anti-HCMV drugs that offer improved efficacy, reduced dosages and options for long-term treatment without risk of the development of viral drug resistance. Recently, we reported the pronounced anti-HCMV efficacy of pharmacological inhibitors of cyclin-dependent kinases (CDKs), in particular, the potential of utilizing drug synergies upon combination treatment with inhibitors of host CDKs and the viral CDK-like kinase pUL97 (vCDK/pUL97). Here, we expand this finding by further assessing the in vitro synergistic antiviral interaction between vCDK and CDK inhibitors towards HCMV as well as non-human cytomegaloviruses. An extension of this synergy approach was achieved in vivo by using the recombinant MCMV-UL97/mouse model, confirming the high potential of combination treatment with the clinically approved vCDK inhibitor maribavir (MBV) and the developmental CDK7 inhibitor LDC4297. Moreover, mechanistic aspects of this synergistic drug combination were illustrated on the levels of intracellular viral protein transport and viral genome replication. The analysis of viral drug resistance did not reveal resistance formation in the case of MBV + LDC4297 combination treatment. Spanning various investigational levels, these new results strongly support our concept, employing the great potential of anti-HCMV synergistic drug treatment.
EVALuna2:545511

Cyclin-Dependent Kinase 8 Represents a Positive Regulator of Cytomegalovirus Replication and a Novel Host Target for Antiviral Strategies - Obergfäll, Debora; Wild, Markus; Sommerer, Mona; Barillas Dahm, Malena; Kicuntod, Jintawee; Tillmanns, Julia; Kögler, Melanie; Lösing, Josephine; Dhotre, Kishore; Müller, Regina; Wangen, Christina; Wagner, Sabrina; et al. (Pharmaceutics, 2024)
Background. Cyclin-dependent kinase 8 (CDK8) is a multifaceted regulator and represents a catalytic component of the transcriptional Mediator complex. CDK8 activity, on the one hand, increases transcriptional elongation by the recruitment of Mediator/super elongation complexes, but, on the other hand, negatively regulates CDK7-controlled transcriptional initiation through inactivating cyclin H phosphorylation. Recently, these combined properties of CDK8 have also suggested its rate-limiting importance for herpesviral replication. Objectives. In this paper, we focused on human cytomegalovirus (HCMV) and addressed the question of whether the pharmacological inhibition or knock-down of CDK8 may affect viral replication efficiency in cell culture models. Methods. A number of human and animal herpesviruses, as well as non-herpesviruses, were used to analyze the importance of CDK8 for viral replication in cell culture models, and to assess the antiviral efficacy of CDK8 inhibitors. Results. Using clinically relevant CDK8 inhibitors (CCT-251921, MSC-2530818, and BI-1347), HCMV replication was found strongly reduced even at nanomolar drug concentrations. The EC50 values were consistent for three different HCMV strains (i.e., AD169, TB40, and Merlin) analyzed in two human cell types (i.e., primary fibroblasts and astrocytoma cells), and the drugs comprised a low level of cytotoxicity. The findings highlighted the following: (i) the pronounced in vitro SI values of anti-HCMV activity obtained with CDK8 inhibitors; (ii) a confirmation of the anti-HCMV efficacy by CDK8–siRNA knock-down; (iii) a CDK8-dependent reduction in viral immediate early, early, and late protein levels; (iv) a main importance of CDK8 for viral late-stage replication; (v) several mechanistic aspects, which point to a strong impact on viral progeny production and release, but a lack of CDK8 relevance for viral entry or nuclear egress; (vi) a significant anti-HCMV drug synergy for combinations of inhibitors against host CDK8 and the viral kinase vCDK/pUL97 (maribavir); (vii) finally, a broad-spectrum antiviral activity, as seen for the comparison of selected α-, β-, γ-, and non-herpesviruses. Conclusions. In summary, these novel data provide evidence for the importance of CDK8 as a positive regulator of herpesviral replication efficiency, and moreover, suggest its exploitability as an antiviral target for novel strategies of host-directed drug development.
CRIS-Team Scopus Importer:2024-10-04
Keywords: antiviral approach with CDK8-inhibitory small molecules; broad-spectrum antiviral CDK8 inhibitors; cyclin-dependent kinase 8 (CDK8); human cytomegalovirus (HCMV); human pathogenic herpesviruses; negative impact of CDK8 inhibitors; novel host-directed targeting strategies; regulation of viral replication; siRNA-mediated CDK8 knock-down; virus-supportive cellular protein kinases

Cyclin‐Dependent Kinases (CDKs) and the Human Cytomegalovirus‐Encoded CDK Ortholog pUL97 Represent Highly Attractive Targets for Synergistic Drug Combinations - Wild, Markus; Hahn, Friedrich; Brückner, Nadine; Schütz, Martin; Wangen, Christina; Wagner, Sabrina; Sommerer, Mona; Strobl, Stefan; Marschall, Manfred (International Journal of Molecular Sciences, 2022)
Human cytomegalovirus (HCMV) is a pathogenic human herpesvirus associated with serious, potentially life‐threatening symptoms in the immunocompromised or immunonaïve host. The limitations encountered by antiviral therapy options currently available include a narrow panel of accessible targets, the induction of viral drug resistance as well as severe drug dosage‐mediated side‐effects. Improved drug‐targeting strategies to resolve these issues are the focus of our investigations. In particular, pharmaceutical kinase inhibitors (PKIs), either directed to host kinases or directed to the viral protein kinase pUL97, have been considered to overcome these restrictions. Recently, we reported the identification of a synergistic combination of two PKIs directed to host cyclin‐dependent kinase 7 (CDK7) and viral CDK ortholog pUL97. Here, we substantiate these findings with the following results: (i) true drug synergy was exhibited by various chemical classes of PKI pairs directed to pUL97 and CDK7; (ii) no putative amplification of cytotoxicity by these drug combinations was observed; (iii) a reduction in drug dosage levels for synergistic combinations was defined on a quantitative basis and compared to monotreatments; (iv) the quantities of target proteins CDK7 and pUL97 expressed in HCMV‐infected cells were assessed by confocal imaging, indicating a strong down‐modulation of CDK7 levels as a result of synergistic drug treatment; (v) the functional importance of these target kinases, both binding to cyclin H, was illustrated by assessing HCMV replication under the viral genomic deletion of ORF‐UL97 or cellular cyclin knock‐out; (vi) new combinations of HCMV‐specific drug synergy were demonstrated for solely host‐directed treatments using PKIs against CDK2, CDK7, CDK8 and/or CDK9 and (vii) a triple PKI combination provided further support for the synergy approach. With these combined findings, this study highlights the potential of therapeutic drug combinations of approved, developmental and preclinical PKIs for expanding future options for anti‐HCMV therapy.
CRIS-Team Scopus Importer:2022-03-04
Keywords: Antiviral drug; Antiviral drug synergism; Cyclin‐dependent kinase (CDK); Direct‐acting antiviral (DAA); Drug combinations; Host‐directed antiviral (HDA); Human cytomegalovirus; New synergistic drug‐target combinations; Pharmaceutical kinase inhibitor (PKI); Viral CDK pUL97 (vCDK)

Development of a PROTAC-based targeting strategy provides a mechanistically unique mode of anti-cytomegalovirus activity - Hahn, Friedrich; Hamilton, Stuart T.; Wangen, Christina; Wild, Markus; Kicuntod, Jintawee; Brückner, Nadine; Follett, Jasmine E.L.; Herrmann, Lars; Kheimar, Ahmed; Kaufer, Benedikt B.; Rawlinson, William D.; Tsogoeva, Svetlana; et al. (International Journal of Molecular Sciences, 2021)
Human cytomegalovirus (HCMV) is a major pathogenic herpesvirus that is prevalent worldwide and it is associated with a variety of clinical symptoms. Current antiviral therapy options do not fully satisfy the medical needs; thus, improved drug classes and drug-targeting strategies are required. In particular, host-directed antivirals, including pharmaceutical kinase inhibitors, might help improve the drug qualities. Here, we focused on utilizing PROteolysis TArgeting Chimeras (PROTACs), i.e., hetero-bifunctional molecules containing two elements, namely a target-binding molecule and a proteolysis-inducing element. Specifically, a PROTAC that was based on a cyclin-dependent kinase (CDK) inhibitor, i.e., CDK9-directed PROTAC THAL-SNS032, was analyzed and proved to possess strong anti-HCMV AD169-GFP activity, with values of EC50 of 0.030 µM and CC50 of 0.175 µM (SI of 5.8). Comparing the effect of THAL-SNS032 with its non-PROTAC counterpart SNS032, data indicated a 3.7-fold stronger anti-HCMV efficacy. This antiviral activity, as illustrated for further clinically relevant strains of human and murine CMVs, coincided with the mid-nanomolar concentration range necessary for a drug-induced degradation of the primary (CDK9) and secondary targets (CDK1, CDK2, CDK7). In addition, further antiviral activities were demonstrated, such as the inhibition of SARS-CoV-2 replication, whereas other investigated human viruses (i.e., varicella zoster virus, adenovirus type 2, and Zika virus) were found insensitive. Combined, the antiviral quality of this approach is seen in its (i) mechanistic uniqueness; (ii) future options of combinatorial drug treatment; (iii) potential broad-spectrum activity; and (iv) applicability in clinically relevant antiviral models. These novel data are discussed in light of the current achievements of anti-HCMV drug development.
CRIS-Team Scopus Importer:2021-12-17
Keywords: Antiviral drugs; Direct-acting antivirals; Host-directed antivirals; Human cytomegalovirus; Human/animal pathogenic viruses; New drug qualities; PROTAC-based targeting strategy; PROteolysis TArgeting Chimeras

Target verification of artesunate-related antiviral drugs: Assessing the role of mitochondrial and regulatory proteins by click chemistry and fluorescence labeling - Hahn, Friedrich; Niesar, Aischa; Wangen, Christina; Wild, Markus; Grau, Benedikt; Herrmann, Lars; Capci, Aysun; Adrait, Annie; Couté, Yohann; Tsogoeva, Svetlana; Marschall, Manfred (Antiviral Research, 2020)
Human cytomegalovirus (HCMV) infection is associated with serious pathology such as transplant rejection or embryonic developmental defects. Antiviral treatment with currently available drugs targeting viral enzymes is often accompanied with severe side effects and the occurrence of drug-resistant viruses. For this reason, novel ways of anti-HCMV therapy focusing on so far unexploited small molecules, targets and mechanisms are intensively studied. Recently, we described the pronounced antiviral activity of the artesunate-related class of trioxane compounds, comprising NF-κB/signaling inhibitors like the trimeric derivative TF27, which proved to be highly active in a nanomolar range both in vitro and in vivo. Here, we extend this analysis by presenting further TF27/artesunate-derived antiviral compounds designed for their specific use in target verification by click chemistry applied in fluorescence labeling and tag affinity strategies. Our main findings are as follows: (i) compounds TF27, BG95, AC98 and AC173 exert strong inhibitory activity against HCMV replication in cultured primary human cells, (ii) autofluorescence activity could be quantitatively detected for BG95 and AC98, and confocal fluorescence imaging revealed accumulation in mitochondria, (iii) postulated cellular targets including mitochondrial proteins were down-regulated upon TF27 treatment, (iv) a click chemistry-based protocol of target enrichment was established, and (v) mass spectrometry-based proteomic analysis, using proteins from HCMV-infected fibroblasts covalently interacting with AC173, revealed a refined list of targets. Combined, data strongly suggest a complex mode of antiviral drug-target interaction of artesunate-related compounds, now highlighting potential roles of mitochondrial, NF-κB pathway proteins, exportins and possibly more. This strategy may further promote antiviral drug development on the basis of pharmacologically optimized trioxane derivatives.
CRIS-Team Scopus Importer:2020-07-10
Keywords: Antiviral experimental drugs; Artemisinin compounds; Click chemistry; Human cytomegalovirus; Proteomics

The Artemisinin-Derived Autofluorescent Compound BG95 Exerts Strong Anticytomegaloviral Activity Based on a Mitochondrial Targeting Mechanism - Wild, Markus; Hahn, Friedrich; Grau, Benedikt; Herrmann, Lars; Niesar, Aischa; Schütz, Martin; Lorion, Melanie M.; Ackermann, Lutz; Tsogoeva, Svetlana; Marschall, Manfred (International Journal of Molecular Sciences, 2020)
Human cytomegalovirus (HCMV) is a major human pathogen associated with severe pathology. Current options of antiviral therapy only partly satisfy the needs of a well-tolerated long-term treatment/prophylaxis free from drug-induced viral resistance. Recently, we reported the strong antiviral properties in vitro and in vivo of the broad-spectrum anti-infective drug artesunate and its optimized derivatives. NF-κB signaling was described as a targeting mechanism and additional target proteins have recently been identified. Here, we analyzed the autofluorescent hybrid compound BG95, which could be utilized for intracellular visualization by confocal imaging and a tracking analysis in virus-infected primary human fibroblasts. As an important finding, BG95 accumulated in mitochondria visualized by anti-prohibitin and MitoTracker staining, and induced statistically significant changes of mitochondrial morphology, distinct from those induced by HCMV infection. Notably, mitochondrial membrane potential was found substantially reduced by BG95, an effect apparently counteracting efficient HCMV replication, which requires active mitochondria and upregulated energy levels. This finding was consistent with binding properties of artesunate-like compounds to mitochondrial proteins and thereby suggested a new mechanistic aspect. Combined, the present study underlines an important role of mitochondria in the multifaceted, host-directed antiviral mechanism of this drug class, postulating a new mitochondria-specific mode of protein targeting.
CRIS-Team Scopus Importer:2020-08-14
Keywords: antiviral drugs; artemisinin derivative; autofluorescence; human cytomegalovirus; intracellular tracking; mitochondrial architecture; mitochondrial impairment; mitochondrial targeting

The trimeric artesunate derivative TF27 exerts strong anti-cytomegaloviral efficacy: Focus on prophylactic efficacy and oral treatment of immunocompetent mice - Wild, Markus; Bertzbach, Luca D.; Tannig, Pierre; Wangen, Christina; Müller, Regina; Herrmann, Lars; Fröhlich, Tony; Tsogoeva, Svetlana; Kaufer, Benedikt B.; Marschall, Manfred; Hahn, Friedrich (Antiviral Research, 2020)
Human cytomegalovirus (HCMV) causes serious and even life-threatening diseases, particularly upon congenital or post-transplant infection. Treatment of HCMV infections with currently available drugs targeting viral enzymes is often limited by severe side effects and the emergence of drug-resistant viruses. To avoid this problem, novel therapeutic options directed to host proteins involved in virus replication are being investigated. Recently, we described the pronounced antiherpesviral activity of the trimeric artesunate derivative TF27 at low nanomolar concentrations in vitro and in vivo. In the present study, we report first data on the prophylactic efficacy of TF27 against human and murine CMV and the oncogenic avian alphaherpesvirus Marek's disease virus (MDV). The main findings of this study are (i) a pronounced activity of the experimental drug TF27 against alpha- and betaherpesviruses in vitro upon prophylactic treatment and (ii) a therapeutic and prophylactic efficacy upon oral treatment in an immunocompetent mouse model. Moreover, our data highlight (iii) the tolerability of orally administered TF27 free of compound-associated adverse events and further confirm (iv) the suitability of cellular factors as primary antiviral targets. Thus, we provide evidence for therapeutic and prophylactic antiherpesviral efficacy of TF27 upon oral treatment in immunocompetent hosts and thereby underline its potential for future antiviral drug development.
CRIS-Team Scopus Importer:2020-04-17
Keywords: Artesunate derivative; Cytomegalovirus; Herpesviral infection model; Host-directed antiviral; Oral administration; Prophylactic efficacy

Understanding the Cytomegalovirus Cyclin-Dependent Kinase Ortholog pUL97 as a Multifaceted Regulator and an Antiviral Drug Target - Marschall, Manfred; Schütz, Martin; Wild, Markus; Socher, Eileen; Wangen, Christina; Dhotre, Kishore; Rawlinson, William D.; Sticht, Heinrich (Cells, 2024)
Herpesviral protein kinases, such as the therapy-relevant pUL97 of human cytomegalovirus (HCMV), are important for viral replication efficiency as well as pathogenesis, and represent key antiviral drug targets. HCMV pUL97 is a viral cyclin-dependent kinase (CDK) ortholog, as it shares functional and structural properties with human CDKs. Recently, the formation of vCDK/pUL97–cyclin complexes and the phosphorylation of a variety of viral and cellular substrate proteins has been demonstrated. Genetic mapping and structural modeling approaches helped to define two pUL97 interfaces, IF1 and IF2, responsible for cyclin binding. In particular, the regulatory importance of interactions between vCDK/pUL97 and host cyclins as well as CDKs has been highlighted, both as determinants of virus replication and as a novel drug-targeting option. This aspect was substantiated by the finding that virus replication was impaired upon cyclin type H knock-down, and that such host-directed interference also affected viruses resistant to existing therapies. Beyond the formation of binary interactive complexes, a ternary pUL97–cyclin H–CDK7 complex has also been described, and in light of this, an experimental trans-stimulation of CDK7 activity by pUL97 appeared crucial for virus–host coregulation. In accordance with this understanding, several novel antiviral targeting options have emerged. These include kinase inhibitors directed to pUL97, to host CDKs, and to the pUL97–cyclin H interactive complexes. Importantly, a statistically significant drug synergy has recently been reported for antiviral treatment schemes using combinations of pharmacologically relevant CDK7 and vCDK/pUL97 inhibitors, including maribavir. Combined, such findings provide increased options for anti-HCMV control. This review focuses on regulatory interactions of vCDK/pUL97 with the host cyclin–CDK apparatus, and it addresses the functional relevance of these key effector complexes for viral replication and pathogenesis. On this basis, novel strategies of antiviral drug targeting are defined.<br
Keywords: herpesviral protein kinases; human cytomegalovirus; cytomegaloviral vCDK/pUL97; regulation of viral replication; impact of vCDK/pUL97; cyclin H and CDK7; antiviral approaches with kinase inhibitors; novel targeting strategies